Implementation of the harmonic transformation method in shape optimization - Żochowski, Antoni (Computer Assisted Methods in Engineering and Science; Vol 5 No 3 (1998), 2023)
The paper describes an implementation of the variant of the speed method in shape optimization for plane elastic structures, based on harmonic transformations. It is coupled with special method for solving the singular elliptic problems resulting from geometric features like e.g. reentrant corners. Both approaches are based on the works of the author. The interactive system has been built, based on MATLAB environment, and the examples showing the robustness of the algorithms were solved.